WOMEN PROPOSITION IN THE INDIAN JUDICIARY - Bandopadhyay, Bipasha (International Journal of Research -GRANTHAALAYAH, 2018)
There have been innumerable debates about gender in India over the years. Much of it includes women’s positing in society, their education, health, economic position, gender equality etc. What one can conclude from such discussions is that women have always held a certain paradoxical position in our developing country. The women position in Indian Judiciary has again been a debatable, topic which has henceforth never been into exact numerical representation. The women clan involved into the legal network of benches has been notably less. The women position has been the highest in the Supreme Court of India with ‘Nine’ Judges. The research work includes statistical data with the research of Vidhi legal policy. “The District Courts and the courts below them comprise the ‘lower’ or ‘subordinate’ judiciary. These courts lie under the administrative control of High Courts. Each judicial district in India has one District Court, below which lie civil and criminal courts of original jurisdiction,” the study notes, and finds that 71% judges in the subordinate judiciary across India are male. Motivation/Background: The women position has been the highest in the Supreme Court of India with ‘Nine’ Judges. The women clan involved into the legal network of benches has been notably less. Method: The fundamental protestant of the research are ‘women’, their count in the benches of Indian Judiciary, specifically over the High Courts and the Supreme Court. So what has been the reason behind such a low count of women? What has been the numerical denomination of women benches in High Courts and Supreme Courts over the past years? Results: Women were relegated to the household, and made to submit to the male-dominated patriarchal society, as has always been prevalent in our country. Indian women, who fought as equals with men in the nationalist struggle, were not given that free public space anymore. They became homemakers, and were mainly meant to build a strong home to support their men who were to build the newly independent country. Conclusions: Women were reduced to being second class citizens. The national female literacy rate was an alarmingly low 8.6%. The Gross Enrolment Ratio (GER) for girls was 24.8% at primary level and 4.6% at the upper primary level (in the 11-14 years age group). There existed insoluble social and cultural barriers to education of women and access to organized schooling.